Reperfusion therapies in elderly and frail patients with pulmonary embolism: a nationwide inpatient sample analysis. (3rd May 2023) - Farmakis, I; Barco, S; Giannakoulas, G; Keller, K; Valerio, L; Ahrens, I; Konstantinides, S V; Hobohm, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although mortality rates have decreased over the last two decades especially for older ages, among patients with PE, age is considered as a significant risk factor for morbidity and mortality. Purpose: To assess the contemporary rates in the use of reperfusion therapies for the management of elderly and frail hospitalized patients with PE and specifically investigate their effect on safety outcomes. Methods: The Nationwide Inpatients Sample (NIS) of years 2016-2018 was accessed to select all hospitalizations of elderly (≥65 years) patients with acute PE as a main discharge diagnosis code or PE as a second-listed diagnosis code following a main discharge diagnosis code for deep vein thrombosis or respiratory failure. We defined frail patients with the use of the Johns Hopkins Adjusted Clinical Groups frailty defining diagnoses indicator, which is an instrument based on ten clusters of frailty defining diagnoses (i.e., malnutrition, dementia, impaired vision, decubitus ulcer, urinary incontinence, weight loss, social support needs, difficulty in walking, and falls). Multivariate logistic regression was used to calculate odds ratios of in-hospital overall and major bleeding among patients who received at least one reperfusion therapy and make two comparisons: (i) systemic thrombolysis (ST) vs catheter-directed thrombolysis (CDT), and (ii) catheter-based thrombectomy (CBT) vs surgical embolectomy (SE). Results: A total of 310, 145 elderly hospitalizations with a primary PE diagnosis were estimated in 2016-2018, of which 66, 745 (21.5%) were frail. Reperfusion therapies were used in 7.0% of all primary PE hospitalizations of elderly people without frailty (35.9% among high-risk patients), while in 4.4% with frailty (24.7% among high-risk patients) (Figure 1). In elderly, CDT was not associated with reduced overall in-hospital bleeding compared to ST (13.6% vs 17.9%, odds ratio [OR] 0.88, 95% confidence interval [CI] 0.73-1.05), but associated with reduced major bleeding (4.9% vs 8.9%, OR 0.68, 95%CI 0.51-0.90) (Figure 2A). Among frail patients, overall bleeding events were significantly fewer in the CDT group compared to ST (14.4% vs 27.6%, OR 0.49, 95%CI 0.31-0.78), although there was no difference in major bleeding (8.4% vs 11.2%, OR 0.85, 95%CI 0.46-1.59) (Figure 2A). Among all hospitalizations of elderly patients who received either CBT or SE, there was difference in overall bleeding events (20% vs 51.7%, OR 0.28, 95%CI 0.17-0.46), but not in major bleeding (8.2% vs 15.7%, OR 0.58, 95%CI 0.27-1.23) (Figure 2B). Among the subgroup of frail patients CBT tended to result in reduced overall bleeding (24.7% vs 45.5% for SE) and major bleeding rates (12.3% vs 27.3%), although without statistical significance (Figure 2B). Conclusion(s): Catheter-directed therapies appear to have a favorable safety profile over ST and SE and may offer an alternative for the high-risk PE management of elderly patients. Figure 1 Figure 2